Refeeding Syndrome Developed in a Patient With Kwashiorkor Can Mimic Findings of Mitochondrial Disorder - Işil Özer (Clinical Medicine Insights: Case Reports, 2022)
Kwashiorkor is a serious nutritional disease. The 7-month-old male patient presented with severe metabolic acidosis and elevated liver enzymes. His condition was similar to fatty acid oxidation defect. He was taken to the hospital on the previous day with complaints of poor sucking and difficulty breathing. Treatment of upper respiratory tract infection was provided and then he returned to his home. He was cyanotic in bed after 12 hours. The patient, who was taken to the hospital unconscious and not fed for 12 hours, was not given any food orally in the first health center. Until laboratory tests are done, only iv electrolyte and a fluid containing dextrose were given. When the laboratory results were found to be significantly pathological, he was urgently referred to our hospital 4 hours after the admission. The content of the iv treatment applied at the time of referral was not clearly written. Low electrolytes, uric acid, liver enzymes, urea and creatinine elevation were detected at an outer center. Ketosis, lactic acidosis and dibasic aciduria were detected in urine organic acid analysis. He was diagnosed with Kwashiorkor and refeeding syndrome according to the clinical and laboratory findings. His complaints improved with appropriate treatment.